HERMENEUTIKA NASR HAMID ABU ZAYD DALAM METODE PERKEMBANGAN TAFSIR MODERN - Muhammad Saekul Mujahidin (IAT IAIN Pontianak, 2023)
In view of the increasingly complex problems of the world and society, the Qur’an must at least be adapted to the conditions of the times and times today. Al-Qur’an interpretation must be able to answer social, economic, cultural, political, religious, and other problems. Nasr Hamid Abu Zayd is a hermeneutic actor who tries to contextualize the Koran in modern times. This research is in the form of library research, where sources are obtained through books, journals or writing related to research. The result of this study is that Abu Zayd interprets the Qur’an in an “objective” manner, namely by applying the approach proposed by Amin al-Khuli, namely the literary approach (al-manhaj al-adabi fi al-tafsir) and the latest theories in linguistics, semiotics and hermeneutics in their studies on the development of modern interpretation. Abu Zayd also tends to use the word ta'wil rather than interpretation. According to him, ta'wil is even broader because it can touch the text and its cultural background.